Exploring the Molecular Mechanism of Homoeopathic Medicines against Cancer: A Pragmatic Approach with Narrative Review of Cell Line Studies - Dixit, Ashish Kumar; Mukherjee, Sukhes; Javed, Danish; Giri, Nibha (Homœopathic Links, 2022)
Background Cancer (CA) is the second leading cause of death, accounting for one out of every six deaths worldwide. Chemotherapy and radiation treatments have unwanted effects and due to financial constraints are not available to a large portion of the population. Many CA patients turn to homoeopathy to improve their quality of life and to relieve pain caused by illness/conventional treatments.Objective The review aims to appraise and summarise the findings of various in vitro CA cell line studies on homoeopathic medicines (HMs) and the detailed molecular mechanism behind the anti-CA effects of HMs.Methods A systematic search was conducted on the major electronic biomedical database PubMed/MEDLINE for articles on homoeopathy and the CA cell line published between 25 June 2011 and 24 June 2021.Result The searches identified 18 relevant articles. HMs showed cytotoxicity, increase in reactive oxygen species and decrease in mitochondrial membrane potential against CA cells while preserving normal cells. It interacts with deoxyribonucleic acid and up- and down-regulation of pro- and anti-apoptotic signalling proteins (p53, caspase-3 and Bax:B-cell lymphoma 2 [Bcl-2]), which all are involved in apoptosis. Increasing the treatment time of CA cells resulted in a higher percentage of cells in the G0/G1 phase (cell cycle arrest) and also showed inhibition of cell migration. HMs also had a complex effect on gene expression profiles.Conclusion This review highlights preliminary laboratory evidence that HMs have therapeutic potential for combating the menace of carcinogenesis. More data are needed to show anti-tumour potential in the current setting and therapeutic value in battling CA.
Keywords: homoeopathy; cancer; cell line; tumour; cell cycle arrest; cytotoxicity; apoptosis; caspase; reactive oxygen species; gene expression